Protein‐Functionalized DNA Nanostructures as Tools to Control Transcription in Zebrafish Embryos. Issue 1 (28th December 2016) - Angelin, Alessandro; Kassel, Olivier; Rastegar, Sepand; Strähle, Uwe; Niemeyer, Christof M.
Abstract: The unique structure‐directing properties of DNA origami nanostructures (DONs) show great potential to specifically manipulate intracellular processes. We report an innovative concept to selectively activate the transcription of a single gene in the developing zebrafish embryo. We reason that engineering a designer transcription factor in which a rigid DON imposes a fixed distance between the DNA‐binding domain (DBD) and the transactivation domain (TAD) would allow the selective activation of a gene harboring the same distance between the corresponding transcription factor binding site and the core promoter. As a test case, a rigid tubular DON was designed to separate the DBD of the GAL4 transcription factor and the VP16 viral protein as a TAD. This construct was microinjected in the yolk of one‐cell‐stage zebrafish embryos, together with a reporter plasmid to assess its functionality. The large DON was efficiently distributed to cells of the developing embryo and showed no signs of toxicity. However, because the DON showed only a cytosolic localization, it did not activate transcription of the reporter gene. Although this work clearly demonstrates that DON microinjection enables the intracellular distribution of multi‐protein architectures in most of the cells of the developing zebrafish embryo, further refinements are necessary to enable selective gene activation in vivo. Abstract : The DON : Three‐dimensional DNA origami rods bearing the regulatory proteins GAL4 and VP16 are investigated for controlling gene expression in a distance‐dependent manner in the developing zebrafish embryo.